Illocutionary Speech Act As A Marketing Strategy For Traders In Panam Morning Market - Fernando Yulistyo Syaputra, Rahmat; Ningsih, Rika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The market is a place where interaction between sellers and buyers occurs. In the process of interaction, someone in expressing an opinion should be a speaker expressing in a language that can be understood together. Language is a sign system of arbitrary, free or arbitrary sounds that community members use to cooperate, interact and identify themselves.  The purpose of this study is to explore and elaborate the form of directive speech acts of panam morning market traders. This type of research is qualitative descriptive research. The commissive speech acts used by traders in peddling their wares were found to be two types of commissive speech acts, namely promising, and offering. After using unique and varied speech, the influence caused by the speech of traders in the Panam morning market was able to attract buyersThe study of directive speech acts and commissive speech acts in interaction speech events in traders in the Panam morning market produced varied findings about the types of directive speech acts and types of commissive speech acts.